The Synthesis Of Group 10 Metals Schiff Base Complexes With Onn And Ons Groups: Characterization And Their Cytotoxicity And Antibacterial Activities - Arafath, Md Azharul (2018)
Twenty-one Schiff base ligands of salicyldehyde derivatives with heterocyclic amine, aniline and carbothioamide were synthesized. The ligands were coordinated to Group 10 transition metals Ni(II), Pd(II) and Pt(II). The synthesized compounds were characterized with physical parameters such as melting point and elemental analysis. These compounds were further characterized with spectroscopic techniques, i.e. FTIR, 1H NMR, 13C NMR, and UV-visible spectroscopy. The structure of most of the ligands were elucidated with single crystal X-ray diffraction analysis. The poly dentate ONS and ONN group containing ligands coordinated via imine nitrogen, phenolic oxygen and thiolate sulphur to form square planar complexes.